Exceptional points in the thermoacoustic spectrum. (27th October 2018) - Mensah, Georg A.; Magri, Luca; Silva, Camilo F.; Buschmann, Philip E.; Moeck, Jonas P.
Abstract: Exceptional points are found in the spectrum of a prototypical thermoacoustic system as the parameters of the flame transfer function are varied. At these points, two eigenvalues and the associated eigenfunctions coalesce. The system's sensitivity to changes in the parameters becomes infinite. Two eigenvalue branches collide at the exceptional point as the interaction index is increased. One branch originates from a purely acoustic mode, whereas the other branch originates from an intrinsic thermoacoustic mode. The existence of exceptional points in thermoacoustic systems has implications for physical understanding, computing, modeling and control.